An ironic twist of fate: replacement name for Stenogyra gracilenta Morelet, 1885, not Achatina gracilenta Morelet, 1867 (Mollusca, Gastropoda, Achatinidae) - Breure, Abraham S.h.; Ablett, Jonathan D. (Zootaxa, 2018)
During work on a monograph of Morelet’s contributions to malacology (Breure, Audibert & Ablett, forthcoming) we found that two of his newly introduced taxa currently have to be considered as homonyms belonging to the genus Subulina H. Beck, 1837 (classified within the family Achatinidae according to Fontanilla et al. (2017: 385)). The older taxon is Achatina gracilenta which was described by Morelet (1867: 79, pl. 7 fig. 2) from [Angola] “Golungo-Alto, au bord du Rio Quiapose, près de Sange; les environs de Lopollo (district de Huilla)”. According to Naggs (1990a: 31; also pers. comm. 10 October 2017) this species has to be classified as Subulina gracilenta (Morelet, 1867). The type material of this species is present in the Natural History Museum, London (NHMUK 1893.2.4.263–265). The younger taxon was described by Morelet (1885: 25, pl. 2 fig. 8) as Stenogyra gracilenta from [Gabon] “environs de Mayumba”. Pilsbry (1906: 82) already recognised this as Subulina gracilenta (Morelet, 1885); Naggs (pers. comm. 10 October 2017) confirmed this classification and concluded that this taxon is a junior secondary homonym of Achatina gracilenta Morelet, 1867. Type material for Stenogyra gracilenta Morelet, 1885 has not been located. We here propose Subulina bruggenorum nom. nov. as a replacement name for Stenogyra gracilenta Morelet, 1885 (not Achatina gracilenta Morelet, 1867).